Observation of the B0s → η′η′ decay - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Physical review letters, 2015)
The first observation of the B0s→η′η′ decay is reported. The study is based on a sample of proton-proton collisions corresponding to 3.0 fb−1 of integrated luminosity collected with the LHCb detector. The significance of the signal is 6.4 standard deviations. The branching fraction is measured to be [3.31±0.64(stat)±0.28(syst)±0.12(norm)]×10−5, where the third uncertainty comes from the B±→η′K± branching fraction that is used as a normalization. In addition, the charge asymmetries of B±→η′K± and B±→ϕK±, which are control channels, are measured to be (−0.2±1.3)% and (+1.7±1.3)%, respectively. All results are consistent with theoretical expectations.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, P. d'Argent, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, K. Matthieu, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D. Mitzel, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 677 weitere]
Im Titel ist "0" hochgestellt und "s" tiefgestellt, dabei steht "0" über "s"
Gesehen am 11.05.2021